Status Epilepticus in Neonates - Saini, Arushi Gahlot; Vinayan, Kollencheri Puthenveettil (International Journal of Epilepsy, 2018)
Seizures are a reflection of acute brain injury in the neonatal period, and status epilepticus reflects a state of high seizure burden. Neonatal status epilepticus has been reported in 8 to 43% of newborns with seizures. There is no separate definition for neonatal status epilepticus, and it has been commonly defined as a continuous seizure lasting at least 30 minutes and/or a series of seizures whose total duration exceeds 50% of a given epoch. The causes of status epilepticus in the neonatal period mirror the causes of neonatal seizures. It is symptomatic, usually associated with hypoxic–ischemic encephalopathy, inherited metabolic disorders, infections, and cerebral hemorrhage. Management guidelines are not separately outlined for neonatal status epilepticus and are commonly derived from the recommendations for neonatal and infantile seizures. The presence of neonatal status epilepticus significantly increases the odds for development of cerebral palsy, global developmental delay, and epilepsy later in life. Further research is needed into the role of current antiepileptic drugs in causing neuronal injury and use of neuroprotective agents during neonatal status epilepticus.
Keywords: neonatal seizures; neonatal status epilepticus; status epilepticus; antiepileptic; brain injury